River Jets Versus Wave-Driven Longshore Currents at River Mouths - Zăinescu, Florin; Anthony, Edward; Vespremeanu-Stroe, Alfred (Frontiers in Marine Science, 2021)
At river mouths, fluvial jets and longshore currents generated by waves interact hydrodynamically. This idealized numerical modelling study simulates a large number of hydro-morphodynamic conditions (650) to explore the emergent hydrodynamics determined by different mouth bar volumes and geometries, river discharge, wave heights and directions and their potential stress on river-mouth development. We find that in the absence of a river-mouth bar (RMB), interactions are driven by momentum balances, expressed either as the balance of wave momentum flux (Mw) and jet momentum flux (Mj), or the balance of river jet discharge (QJet) and longshore current discharge (QLSC). When a RMB is present, the topography modifies the structure of the jet by spreading it, and we quantify this mechanism through the lateral jet spreading index (LJT). Secondly, topography generates complex longshore wave-driven circulation as a result of the protruding shoreface which serves as a platform on which counter longshore currents develop. The balance in QJet/QLSC may be used as an indication of the type of circulation. High and oblique waves favor longshore circulation and RMB bypass, whereas low waves and normal-to-coast angles generate diverging longshore currents on the mouth bar crest which interrupts the longshore circulation. A quantification of the dynamic diversion is proposed in the form of the non-dimensional dynamic diversion index (DyD), which scales with the product of Mj and Mw, and can account for the absolute strength of hydrodynamic interactions occurring at river mouths. RMB morphology can affect DyD in multiple ways by strengthening or by weakening the interactions. The DyD effect seems to increase with increasing RMB size, indicating that the RMB scale regulates the interplay of the wave-driven circulation and the river jet which further controls the adjacent topography changes.